(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
Convergingupon the degradation of several sides of our environment and culture Arundhati Roy as an activist shows her concern in her novel The God of Small Things over all kinds of oppression resulted from the devastating consequence of the global market, development happened without sustainable thought and the locus of women in the postcolonial society. Roy highlights the necessity of social, economic and environmental justice for oppressed women, marginalised human beings and nature. Patriarchal categories always ignore productive and sustainable activities and adore unproductive activities and so development which creates uneven structures and environmental poverty is assessed as mal-development. Roy focuses on how hierarchical development and commercial development together damage the entire ecology of Ayemenem where Ammu and her twinsRahel and Estha are victimised most. The emergence of westernisation not only affects Indian culture and nature leading towards profit-orientedviewpoint but seizesthe purity and wilderness embedded in it also.Therefore, this novel aims at showing Roys presentation of women, culture and nature from the viewpoint of ecology and feminism.